Direct evidence for human exploitation of birds in the Middle Stone Age of South Africa: The example of Sibudu Cave, KwaZulu-Natal. Issue 99 (October 2016) - Val, Aurore; de la Peña, Paloma; Wadley, Lyn
Abstract: Here, we present direct taphonomic evidence for the exploitation of birds by hunter-gatherers in the Middle Stone Age of South Africa as far as ∼77 ka. The bird assemblage from Sibudu Cave, KwaZulu-Natal, was analysed for bone surface modifications. Cut-marks associated with skinning, defleshing, and disarticulation, perforations on distal humeri produced during disarticulation of the forewing, peeling, and human tooth marks were observed on bird bones (i.e., mostly pigeons, doves, Galliformes, waders, and raptors) recovered from pre-Still Bay, Still Bay, Howiesons Poort, and post-Howiesons Poort techno-complexes. We conducted experiments to butcher, disarticulate, cook, and consume pigeon and dove carcasses, in order to create a comparative collection of bone surface modifications associated with human consumption of these birds. Human/bird interactions can now be demonstrated outside of Europe and prior to 50 ka. The evidence sheds new light on Middle Stone Age subsistence strategies in South Africa and introduces a fresh argument to the debate regarding the early emergence of behaviours usually associated with Later Stone Age hunter-gatherers.